1978
DOI: 10.1017/s0021932000011743
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behaviour and contraceptive practice of undergraduates at Oxford University

Abstract: At the end of the 4th week of the Hilary Term 1977, 1006 male and 1009 female undergraduates at Oxford University were sent a questionnaire enquiring about their sexual behaviour and contraceptive practice. Of the 862 women and 634 men who replied, 512 women (59%) and 332 men (52%) had experienced sexual intercourse, 396 women and 191 men in the 4-week period preceding receipt of the questionnaire. No contraception had been used by 27 % of the women on the first occasion that they had had intercourse; during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1981
1981
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…As discussed earlier, Kantner and Zelnik (1973;Shah et al, 1975;Zelnik & Kantner, 1977) did find that women's contraceptive use increases with age. Other studies with younger adolescent respondents found similar effects (Furstenberg et al, 1983;Herold, 1981b;Steinlauf, 1979), but most studies of college-age subjects did not (Anderson et al, 1978;DeLameter & Mac-Corquodale, 1979;Hill, Peplau, & Rubin, 1983;Reissetal., 1975).…”
Section: Demographic Differencesmentioning
confidence: 90%
See 2 more Smart Citations
“…As discussed earlier, Kantner and Zelnik (1973;Shah et al, 1975;Zelnik & Kantner, 1977) did find that women's contraceptive use increases with age. Other studies with younger adolescent respondents found similar effects (Furstenberg et al, 1983;Herold, 1981b;Steinlauf, 1979), but most studies of college-age subjects did not (Anderson et al, 1978;DeLameter & Mac-Corquodale, 1979;Hill, Peplau, & Rubin, 1983;Reissetal., 1975).…”
Section: Demographic Differencesmentioning
confidence: 90%
“…Differences in contraceptive use between Catholics, Protestants, and Jews are quite small (Anderson et al, 1978;Angrist, 1966;Garris etal., 1976;Geis&Gerrard, 1984;Goldsmith etal., 1972;Hill etal., 1983;Kantner & Zelnik, 1973). The major denominational difference in contraceptive use found by Kantner and Zelnik is intra-Protestant between fundamentalists and nonfundamentalists.…”
Section: Demographic Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequency of sexual encounters is positively related to contraceptive use (Anderson et al, 1978;Cvetkovich & Grote, 1981;Foreit & Foreit, 1978;Geis & Gerrard, 1984). Infrequent sexual activity is often stated as a reason for sporadic use or non-use of contraception (Evans, Selstad & Welcher, 1976;Zelnick & Kanter, 1977), though Herold & McNamee (1982) found no direct association between frequency of intercourse and efficient contraceptive use.…”
Section: Introductionmentioning
confidence: 99%
“…In 1971, 45% of single female undergraduates at Aberdeen University who were sexually active did not always use satisfactory contraceptive methods (McCance & Hall, 1972), compared to 10% at Oxford University in 1977 (Anderson et al, 1978). The greater use of contraception at Oxford was interpreted as due to a better awareness and availability of contraceptive services that occurred during the 6-year interval between the two studies.…”
Section: Introductionmentioning
confidence: 99%